2006
DOI: 10.1111/j.1365-2036.2006.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of organ‐ and non‐organ‐specific autoantibodies on the response to anti‐viral treatment of patients with chronic hepatitis C

Abstract: SUMMARY BackgroundDevelopment of organ-and non-organ-specific autoantibodies has been reported in hepatitis C virus patients treated with interferon-a plus/minus ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
(190 reference statements)
0
21
0
3
Order By: Relevance
“…The histologic evaluation for inflammation and fibrosis was assessed using the Knodell histologic activity index [28] . According to previous publications of our group [29][30][31] , for statistical reasons the patients were divided into two groups: (1) according to inflammation: minimal/mild (score 0-8) and moderate/severe (score 9-18); and (2) according to fibrosis: none/mild (score 0-1) and moderate/severe/cirrhosis (score 2-3).…”
Section: Patientsmentioning
confidence: 99%
“…The histologic evaluation for inflammation and fibrosis was assessed using the Knodell histologic activity index [28] . According to previous publications of our group [29][30][31] , for statistical reasons the patients were divided into two groups: (1) according to inflammation: minimal/mild (score 0-8) and moderate/severe (score 9-18); and (2) according to fibrosis: none/mild (score 0-1) and moderate/severe/cirrhosis (score 2-3).…”
Section: Patientsmentioning
confidence: 99%
“…Circulating autoantibodies, including antinuclear antibodies (ANA), RF, antiphospholipid (aPL) antibodies, cryoglobulins, anti-smooth muscle actin (SMA) antibodies, liver-kidney microsomal antibodies (LKM), and antithyroid peroxidase, are often detected in patients with chronic HCV infection [3,74,75]. ANA, RF and SMA are the most common.…”
Section: Autoantibodies Associated With Chronic Hcv Infectionmentioning
confidence: 99%
“…Gatselis et al [74] found a negative correlation between the efficacy of antiviral treatment for HCV and the presence of ANA and SMA before treatment and their increase during therapy. A highly favourable treatment response was associated with an absence of ANA and a decrease in SMA titres during therapy.…”
Section: Autoantibodies Associated With Chronic Hcv Infectionmentioning
confidence: 99%
“…Hierzu gehört das Auftreten von Autoantikörpern, welche durch Aktivierung von B-Lymphozyten durch das Virus entstehen und zu vaskulitischen Krankheitsbildern mit pulmonaler Hämorrha-gie und Glomerulonephritis führen kön-nen [10]. In einer Reihe von Studien ist die Prävalenz von Autoantikörpern -am häufigsten die von Rheumafaktoren, antinukleären Antikörpern (ANA), antimitochondrialen Antikörpern (AMA), Antikörpern gegen glatte Muskulatur (AS-MA), Liver-Kidney-Microsomes-Antikörpern (LKM) und Schilddrüsenanti-körpern -bei Patienten mit chronischer Hepatitis-C-Infektion untersucht worden [2,7,11] [4,10]. Insgesamt bleibt die klinische Relevanz der bei Patienten mit Hepatitis C nachgewiesenen Autoantikör-per aber häufig unklar und geht in vielen Fällen nicht mit einer entsprechenden klinischen Manifestation einher.…”
Section: Hepatitis C Und Autoimmunitätunclassified